Course reserves module: make the connection - Amno, Hasniza; Md Rashid, Mohd Nasir; Abdul, Mustaqeem; Abdullah Sani, Wan Linda Suryanti; Shaharuddin, Bakiah (Universiti Teknologi MARA, Kedah, 2017)
KOHA is an open source integrated library system which has been used by USM Library since 2009. KOHA’s system comprises web based modules which include course reserves, circulation, cataloging, acquisitions, serials, reservation, patron management and branch relationships. One of the most important modules is course reserves. Course reserves are course-related items for academic programs offers in the University. The course reserves collections contain required course reading materials including textbooks, thesis, CD-ROMS, journals and other items in the library collections. In Malaysia, USM Library is the first university that utilizes the course reserves module among other KOHA academic library users. The library of the Advanced Medical and Dental Institute (AMDI) is the first USM Library branches which initiated this module for the benefits of their students and academic faculty. At AMDI, we offer various post graduate programs (Masters and PhD, including Mixed Mode and coursework programmes). Briefly, all the academic program heads and lecturers collaborated with the librarians to compile a comprehensive list of learning materials in any formats (books, journal, media, etc.) for each programme. When the students embark on a new study, they were provided with programme outcomes and course learning objectives which will be their targeted objectives at the end of their study. To achieve this, the students will be assisted with lists of recommended learning materials by the programme heads. Through the Course Reserves module accessible from the Online Public Access Catalog (OPAC), students are given the opportunity to view and monitor all the library materials placed by the lecturers to fulfil all the course learning outcomes for each course. The materials are course specific and can be continuously updated from time to time by the programme heads according to the demands of the courses and relevant to the current needs of the students and lecturers. Students may search by the course number, course name or lecturer's name. KOHA integrated library system provides updated course materials on the library OPAC for easy access from different locations at all times. This information includes loan availability, location of the materials, call number and more. As a result, by June 2017, AMDI Library had completed preparing the course reserves module for 7 academic programmes; M.Sc in Health Toxicology, M.Sc in Oral Science, M.Sc in Clinical Exercise Science, M.Sc in Medical Research, M.Sc Transfusion Science and Master in Medicine (Transfusion Medicine), Master in Medicine (Nuclear Medicine).